Morpho-anatomical characterization and DNA barcoding of Achillea millefolium L. - MOCHAMMAD ILHAM; SITI RIZQIYATUL MUKARROMAH; GALUH AYU RAKASHIWI; DANI TRI INDRIATI; BRUNI FLARANDA YOKU; PUTUT RAKHMAD PURNAMA; JUNAIRIAH JUNAIRIAH; SEHANAT PRASONGSUK; HERY PURNOBASUKI; DWI KUSUMA WAHYUNI (Society for Indonesian Biodiversity, 2022)
Abstract. Ilham M,Mukarromah SR, Rakashiwi GA, Indriati DT, Yoku BF, Purnama PR, Junairiah, Prasongsuk S,Purnobasuki H, Wahyuni DK. 2022. Morpho-anatomical characterizationand DNA barcoding of Achillea millefolium L. Biodiversitas 23: 1958-1969. One of the important things to study the distribution of secondary metabolites in the plant body is to carry out the identification process. Morphological markers have several limitations to recognize plants, therefore supporting data is needed so that the information becomes more comprehensive. This study aims to identify Achillea millefolium L. based on morphological, anatomical, and DNA barcoding markers to obtain specific data and avoid confusion. Morphological studies were carried out descriptively using vegetative organs, while anatomical studies of rhizomes, stems, and leaves used the paraffin method. The DNA barcoding was performed by analyzinggenes from 3 different individuals. The research was carried out by amplifying and sequencing the partial gene in the ribulose-bisphosphate carboxylaselarge subunit (rbcL) regions and maturase-K (matK). The results showed that the plant had taproots, short stems due to root rosette and the leaves were double compound. The rhizome and stem tissues had almost the same structure, while the leaves had a tissue arrangement that was similar to other plants in general, except that the mesophyll tissue was undifferentiated. The results of DNA barcoding showed a percentage of identity above 98% for both the rbcLand matK genes.